Emotion‐related impulsivity and suicidal ideation: Towards a more specific model. (1st August 2022) - Anvar, Sarah; Swerdlow, Benjamin A.; Jobes, David; Timpano, Kiara R.; Mandel, Abby Adler; Kleiman, Evan; Joiner, Thomas; Johnson, Sheri L.
Abstract: Objectives: Suicidal ideation is a pervasive and painful experience that varies considerably in its phenomenology. Here, we consider how one key risk variable might inform our understanding of variation in suicidal ideation: emotion‐related impulsivity, the trait‐like tendency towards unconstrained speech, behaviour, and cognition in the face of intense emotions. We hypothesized that emotion‐related impulsivity would be tied to specific features, including severity, perceived lack of controllability, more rapidly fluctuating course, higher scores on a measure of acute suicidal affective disturbance, and more emotional and cognitive disturbance as antecedents. Methods: We recruited two samples of adults ( N s = 421, 221) through Amazon Mechanical Turk (MTurk), with oversampling of those with suicidal ideation. Both samples completed psychometrically sound self‐report measures online to assess emotion‐ and non‐emotion‐related dimensions of impulsivity and characteristics of suicidal ideation. Results: One form of emotion‐related impulsivity related to the severity, uncontrollability, dynamic course, and affective and cognitive precursors of ideation. Conclusions: Despite limitations of the cross‐sectional design and self‐report measures, the current findings highlight the importance of specificity in considering key dimensions of impulsivity and suicidal ideation.